RETRACTED: Multicomponent siRNA/miRNA-loaded modified mesoporous silica nanoparticles targeted bladder cancer for a highly effective combination therapy - Shahidi, Maryamsadat; Abazari, Omid; Dayati, Parisa; Bakhshi, Ali; Zavarreza, Javad; Modarresi, Mohammad Hossein; Haghiralsadat, Fateme; Rahmanian, Mehdi; Naghib, Seyed Morteza; Tofighi, Davood (Frontiers in Bioengineering and Biotechnology, 2022)
Bladder cancer is one of the concerning urological malignant diseases in the world, which has a clinical need for effective targeted therapy. The development of nanotechnology-based gene delivery to bladder tumor sites is an effective strategy for targeted cancer therapy with low/no toxicity. With this view, in the present work, the mesoporous silica nanoparticles (MSNs) modified with c(RGDfK)-PLGA-PEG (c(RGDfK)-MSN NPs) were constructed for co-delivery of miR-34a and siPD-L1 within bladder cancer cells and tissues. Our findings showed that miR-34a is down-regulated, while PD-L1 was up-regulated in cell lines and animal study. This nano-carrier is biocompatible in the serum environment and effectively protects miR-34a and siPD-L1 against serum degradation. However, we showed that c(RGDfK)-MSN NPs could simultaneously downregulate PD-L1 expression and up-regulate miR-34a in the T24 cells and T24 mice model and enhance anti-tumor effects both in vivo and in vitro. In conclusion, these findings presented new suggestions for improving targeted therapeutic strategies with specified molecular objectives for bladder cancer treatment.